C-Reactive Protein a Suitable Marker for Heavy Metal Toxicity: A Comparative Study for Two Freshwater Fish Species Response to Cadmium - Alaa J. Hassan (Journal of Global Pharma Technology, 2017)
The present study estimate some blood parameters including, total and differential white blood cells (WBCs) count, red blood cells (RBCs) count, hemoglobin (Hb) level and packed cell volume percentage (PCV%), as well as the concentrations of serum total protein and C – reactive protein (CRP) in two species of Iraqi freshwater fishes (CyprinusCarpio and Hypophthalimchthyes molitrix) exposed to two concentration of cadmium (cd) (0.5 and 1) pep. Fishes exposed to cd in glass basins for 7 and 14 days with five replicate for each treatment and control groups .Results: The results showed that there was a significant differences (p<0.05) in the total WBCs count, monocytes (MON),granulocytes (GRA) and RBCs between individuals of both treated species in each period and treatment , but there was a significant decreases (p<0.05) for this parameters in treated silver carp group compared with silver control group, furthermore , there was a significant decrease PCV% in silver fishes treated with cd , as well as there was a significant decrease in the level of Hb for both treated species compared with healthy subject . The data revealed that there is a significant differences (p<0.05) in the concentration of total serum protein between individuals of both treated species in each period and treatment, but there was a significant decrease (p<0.05) in the level of this parameter in treated H. molitrix groups compared with control group, furthermore, the level of CRP revealed that significant increase in different periods and level of pollutant in both treated fishes groups compared with healthy subject. Conclusions: The results displays that there is a significant differences (p<0.05) in the levels of blood parameters between treated species of fishes, and H. molitrix fish was more sensitive to cd in comparison with treated C. carpio and control group, also there was a significant difference in the levels of total serum protein and CRP in treated fishes compared with control groups.Keywords: Cyprinus Carpio, Hypophthalimchthyes molitrix, Cadmium, Hematology, Immunology